Study of Lapsi Fruits Enterprise Opportunities - Joshi, Rinita Rajbhandari (Journal of the Institute of Engineering, 2018)
Choerospondias axillaris is locally known as Lapsi in Nepal. The study of enterprises of Lapsi fruits production and its uses in market was conducted in September, 2015 in Bhaktapur district and Kalimati Fruits and Vegetable Wholesale Market, Kathmandu, Nepal. The major objectives were to study Lapsi fruits enterprises and its uses in different sectors. Lapsi fruits are sold in wholesale and retail price in Kalimati Fruits and Vegetable Wholesale Market. In Bhaktapur, Lalitpur and Kathmandu districts, the production areas covered were 198.0, 15.0 and 55.0 hectare, total productions were 105.0, 150.0 and 405.0 metric ton with productivity of 0.9, 10.0 and 7.4 metric ton per hectare respectively. The total Lapsi fruits production area, total production and productivity were 1503.0 hectare, 10488.0 metric ton and 7.4 metric ton per hectare in Nepal. The monthly maximum price of Lapsi fruits was NRs.30.00/kg in July/ August 2015. Similarly, the maximum price reached up to NRs.110.0 in February/March. The pulp of the Lapsi fruits is use preparing Lapsi powder, candy and it’s seed stone can be use for the preparation of activated carbon. Government policies should be clear about increase in production and productivity by the help of subsidy inputs. Farm get price should be reasonable. Lapsi candy processing and activated carbon production industries should be promoted where Lapsi fruits are cultivated. Hygienic candy and activated carbon should be exported to neighboring countries and overseas. It helps to earn foreign currency and develop economic of the country. Journal of the Institute of Engineering, 2017, 13(1): 145-152